Orbital complications following extraction of mandibular molar teeth: a case report. (11th September 2018) - French, K.; Jagsi, A.; Main, B.G.; Thomas, S.J.
Abstract: Serious sequelae of dental infections are unusual but can be potentially life‐ or sight‐threatening. This case describes the rapid and extensive development of a fascial space infection through an uncommon route, originating in mandibular molar teeth to involve the orbital tissues. Relevant surgical anatomy and pathophysiology are discussed. Also highlighted is the multidisciplinary management of care across three surgical specialities with input from the radiology and microbiology teams.